Sacrococcygeal heart - Kazez, A; Özercan, IH; Erol, FS; Özveren, MF; Parmaksiz, E (Georg Thieme Verlag Kg, 2002)
A mature teratoma was identified in a two-month-old girl who was operated for a sacrococcygeal mass. The cystic components of the mass were accidentally opened during surgery, and a solid, rudimentary organ resembling a heart emerged. It had a vascular pedicle and a pulsation like cardiac activity different from the infant's heart rate. The mass was totally excised together with the coccyx, and in histological examinations, it was diagnosed as a mature teratoma and a rudimentary heart. To the best of our knowledge, the case presented in this report is only the second case of a cardiac development in a teratoma in the literature. In the light of data obtained about this case and related literature, we consider that fetus-in-fetu and teratoma may not be irrelevant entities, and that they possibly have the same developmental malformation. We also suggest that such an intermediate case is a combination of fetus-in-fetu and teratoma.
4th European Congress of Paediatric Surgery -- MAY 03-05, 2001 -- BUDAPEST, HUNGARY
Keywords: teratoma; fetus-in-fetu; sacrococcygeal